Impact of Civil Envelope on Energy Consumption based on EnergyPlus. (2015) - Yu, Shui; Cui, Yumeng; Xu, Xiaolong; Feng, Guohui
Abstract: In this paper, a rural residential model located in Shenyang is established by simulation software DesignBuilder. Simulation process is divided into the following conditions, variety of thermal performance walls, roofs and windows. Building energy consumption was simulated through EnergyPlus under different conditions. The information of EnergyPlus and modelling process are referred. Impact of envelope heat consumption for various thermal performance and the energy saving potential are analysed. This research provides technical support and theoretical guidance for new energy efficient building and renovation projects.